Developing programming skills on digital native children through the interaction with smart devices - ROCHA, José Rafael Moraes Garcia da (2016)
Nowadays the computational thinking is one of the most important skills a person should develop to be more well prepared for the near future. By the middle of this century, this ability will probably have the same level of importance of fundamental skills like reading and writing, and people will need to learn programming and problem solving with computational thinking from an early age. Studies are trying to stimulate the introduction of this skill set to young children, and this has been done since 1967 when the Massachusetts Institute of Technology created the first language aiming this kind of public called LOGO. Although the studies in the area of developing computational thinking on children started almost six decades ago, the importance of teaching programming in schools is not widely spread, in places like Brazil, this skill is starting to be introduced to children older than 10 yearsold. In contrast, the United States and some european countries are using a variable set of approaches to introduce these concepts to young children varying from 4 to 12 years old, usually by creating toys and games which these concepts can be developed within them. Unfortunately most of approaches are aimed for already literate children, very few of them do not require reading skills, limiting the minimum age of users to approximately 6 years old. This work has the intention to argue that toddlers are not only able to develop algorithms and initiate the development of computational thinking skills, but also this practice will be quite profitable for their future. A survey involving 9 children with between 4 and 6 years old is presented, where the selected children played a game developed specially for this work, and their performance was able to produce data that is going to be analyzed further to test the main hypothesis which is " Toddlers can develop algorithmic thinking by playing programming games ", additionally, while reviewing the literature, problems related to the effects of letting children use smart devices and internet without supervision were identified, in order to advocate the usage of this technology by young children, possible causes and risks of these problems are presented and ways to avoid them as well, the results of this work are encouraging, all toddlers involved were able to play the game developed.